Analisis Faktor Makro dan Mikroekonomi terhadap Harga Saham Perusahaan Perbankan Digital - Panca Fatikhul Inami; Muttaqiin, Ninnasi (JURNAL AKUNTANSI DAN MANAJEMEN, 2024)
This research aims to determine the influence of macro and micro economic factors on share price fluctuations in digital banking sector companies listed on the Indonesian Stock Exchange (BEI) during the 2020-2023 period. Share prices in this study are used as the dependent variable. Meanwhile, the independent variables used in this research are inflation, interest rates, exchange rates, GDP, broad money supply, EPS, PER, BVPS, ROA, ROE, company size, capital structure, and CR. The data management method used is multiple linear regression analysis. The findings show that simultaneously, the variables inflation, interest rates, exchange rates, GDP, broad money supply, EPS, PER, BVPS, ROA, ROE, company size, capital structure and CR significantly affect stock prices. The variables interest rate, broad money supply, PER, BVPS, and CR partially have a significant effect on stock prices. Meanwhile, the variables inflation, exchange rate, GDP, EPS, ROA, ROE, company size and capital structure partially do not have a significant effect on stock prices.